2015
DOI: 10.1039/c4ra13072c
|View full text |Cite
|
Sign up to set email alerts
|

Controllable synthesis of fluorapatite microcrystals decorated with silver nanoparticles and their optical properties

Abstract: An EDTA-assisted hydrothermal method is developed for the controlled preparation of fluorapatite microcrystals (FHAp MPs) decorated with silver nanoparticles (Ag NPs). The synthesis process involves the use of EDTA as both a chelating agent and a reducing agent, allowing the one-pot formation of Ag/FHAp composites. The resultant product was characterized by X-ray diffraction patterns (XRD), field emission scanning electron micrographs (FESEM), transmission electron microscopy (TEM), and UV-vis diffuse reflecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…These results indicate that metallic Ag NPs have formed on the surface of FAP crystals and that did not enter into the structure. Also, the diffractogram of FAP crystals decorated with Ag NPs is showing peaks originating from elemental silver, and confirm that the silver did not enter into the crystal lattice [30]. In the case of our samples, XRD diffractograms confirmed that the single phase material is obtained, which is also the proof of the Ag + substitution into the FAP crystal lattice [20].…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…These results indicate that metallic Ag NPs have formed on the surface of FAP crystals and that did not enter into the structure. Also, the diffractogram of FAP crystals decorated with Ag NPs is showing peaks originating from elemental silver, and confirm that the silver did not enter into the crystal lattice [30]. In the case of our samples, XRD diffractograms confirmed that the single phase material is obtained, which is also the proof of the Ag + substitution into the FAP crystal lattice [20].…”
Section: Resultssupporting
confidence: 69%
“…With increase of dopant concentration charge transfer absorption band becomes more intensive and sharper, and proves a high efficiency of the energy transfer between the host lattice and the dopant ions. Study of optical properties of FAP microcrystals decorated with silver nanoparticles (Ag NPs) has shown that absorption of composite samples has maximum at 400 nm which can be associated with the characteristic of the surface plasmon resonance of Ag NPs [30]. These results indicate that metallic Ag NPs have formed on the surface of FAP crystals and that did not enter into the structure.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, various nanotechnologies have been designed in the field of biomedicine and have received extensive attention 4‐7 . The hydroxyapatite (HAp, Ca 10 (PO 4 ) 6 (OH) 2 ) is a primary inorganic composition of mammalian hard tissues (bone and teeth), as a biomaterial scaffold with good biocompatibility and biodegradability, the nano‐HAp (nHAp) and F‐substituted nHAp (nFAp) were widely used in the biomedical field 8‐11 . Recently, a variety of bioimaging systems based on nHAp have been prepared for dual/multi‐mode tracking 12‐14 .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] The hydroxyapatite (HAp, Ca 10 (PO 4 ) 6 (OH) 2 ) is a primary inorganic composition of mammalian hard tissues (bone and teeth), as a biomaterial scaffold with good biocompatibility and biodegradability, the nano-HAp (nHAp) and F-substituted nHAp (nFAp) were widely used in the biomedical field. [8][9][10][11] Recently, a variety of bioimaging systems based on nHAp have been prepared for dual/multi-mode tracking. [12][13][14] In general, the construction of nHAp imaging probes is achieved by post-modifying various imaging contrast agents through physical or chemical interaction such as gold nanoparticles, quantum dots and carbon dots.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Due to the quantum confinement effect, 25,26 nano-sized HAp and FAp are widely used in catalysts, sensors, tissue engineering, biomedical fields, and environmental phosphorus recovery. [27][28][29] Furthermore, nano-HAp and its counterparts have been successfully demonstrated to be efficient building blocks, biocompatible scaffolds or multifunctional bio-nanoplatforms, [30][31][32][33][34] with the loading of several fluorescence imaging agents for tar- † Electronic supplementary information (ESI) available: Experimental details of monodispersed NFAp and cell incubation; quantum yield measurements of CDs and CDs-COOH; PL spectra of CDS-COOH@PEA-NFAp conjugates with different weight ratios in Fig. S1; excitation-dependent PL spectra of CDs-COOH in Fig.…”
Section: Introductionmentioning
confidence: 99%